The association of concussion history and symptom presentation in combat sport athletes. (March 2021) - Brown, Daniel A.; Grant, Gary; Evans, Kerrie; Leung, Felix T.; Hides, Julie A.
Abstract: Objective: The purpose of this study was to describe the concussion-related symptoms reported among combat sport athletes with and without a history of concussion, and a history of neck injury. Design: Cross-sectional survey. Setting: Data were collected using an online survey instrument. Participants: Three hundred and nine adult combat sport athletes. Main outcome measures: Self-reported 12-month concussion history and neck injury history and a 22-item symptom checklist. Results: A history of concussion was reported by 19.1% of athletes, a history of neck injury was reported by 23.0%, and 13.6% reported both injuries. Neck pain was the most frequently reported symptom. Athletes with a history of injury had significantly greater proportions of 'high' total symptoms and symptom severity scores compared with athletes with no history of injury. Athletes with a history of concussion had 2.35 times higher odds of reporting 'high' total symptoms and symptoms severity scores. Conclusion: Athletes with a history of concussion or neck injury have greater odds of presenting with higher symptom scores. The presence of high total symptom scores and high symptom severity scores may indicate a need for further investigation into domains commonly associated with concussion. Highlights: Although concussion is prevalent in combat sports, athletes appear to not seek medical attention. Many combat sport athletes return to contact after 2 days following a concussion. Combat sport athletes with a history of concussion report higher concussion-related symptoms. Athletes with a history of concussion and a history of neck injury have greater odds of presenting with high symptom scores.